Del colonialismo a la Primera Guerra Mundial Desestructuración de los pueblos de África - Axel Riveros Vera (Grafía, 2014)
The present research assessment offers a theoretical approach to the origin and expansion of colonialism at the end of 19th century of Europe in Africa, within an intercultural approach, which has been built by academic groups and social communities which have lived a process of historical silence in our region and in most of the countries of Latin America. There’s a theoretical approach to Imperialism and Colonialism in order to study the configuration to the geographical and social space in Africa. It ends with some provisional conclusions derivated from the current work.